Copyright in Artificial Intelligence Generated Results - Poghosyan, Nune; Hovhannisyan, Arpine (Bulletin of Yerevan University C: Jurisprudence, 2023)
The paper discusses the possibility of protecting artificial intelligence results under copyright from the point of view of the author of the work, the conditions of protection and the rights granted as a result of protection. In modern world, artificial intelligence creates works that, if created by humans, would inevitably be considered copyrighted works and would be subject to legal protection. There is still no unified approach to the recognition of copyright to the results created by artificial intelligence, while the solution to this issue can be of theoretical and practical importance.In the course of the research, general philosophical and traditional-legal methods were used. The research was based on both legal sources (RA Law on Copyright and Related Rights, Berne Convention, judgements of the RA Court of Cassation and foreign courts), as well as scientific works such as published books, scientific articles, etc.The article raises the question of the possibility of legal protection of works created by artificial intelligence within the framework of other legal structures, including the legal regulations regarding the persons organizing the creation of the work.
Keywords: artificial intelligence; copyright; author; creativity; originality; moral rights; persons organizing the creation of the work